E-complaint system for UiTM Perlis college embedded with gamification / Afifah Najibah Arif ... [et al.] - Arif, Afifah Najibah; Othman, Mahfudzah; Muhd Zain, Nurzaid; Paidi, Zulfikri (UiTM Cawangan Perlis, 2022)
Even though people can make complaints through a computerized system, some places still use the manual system. The manual system is inconvenient for the complainant because they must visit the respective counter to channel the complaints. In addition, the form provided usually consists of long instructions for the complainant to read before channelling the complaint. This paper discusses the development of an e-Complaint System for UiTM Perlis colleges embedded with gamification. In this system, there are three gamification elements included, which are the progress bar, leaderboard, and Avatar selection for personalization. Two tests were conducted, which are functionality and usability testing through various platforms such as YouTube, 000webhost, and Google Form. There were 33 respondents for the usability testing consisting of students and staff of UiTM Perlis. While the functionality testing was conducted with UiTM Perlis lecturers who have experienced teaching IT subjects. From the responses obtained from the respondents through PPSUQ Survey, most of the respondents agreed that the developed system helped them in channelling complaints and updating the status of their complaints compared to the existing system. The system developed does include some gamification elements which can ease the users to use the e-complaint system in the future. Via this system, users were guided on how to lodge complaints via step-by-step process instead of reading long instructions which could lead them to confusion.